A systematic review and meta-analysis of yoga for arterial hypertension. - Christoph Geiger; Holger Cramer; Dennis Anheyer; Gustav Dobos; Wiebke Kathrin Kohl-Heckl (PLoS ONE)
Background This systematic review and meta-analysis is an update to prior research to evaluate the effects of yoga for managing prehypertension and hypertension. Methods Medline/PubMed, Scopus and the Cochrane Central Register of Controlled Trials (CENTRAL) were searched from their inception until April 5th 2024. Randomized-controlled trials (RCTs) that compared yoga to any control intervention in participants with diagnosed prehypertension (120-139/80-89 mmHg) or hypertension (≥140/ ≥ 90mmHg) were included. Mean differences (MD) and 95% confidence intervals (CI) were calculated. Risk of Bias was assessed using the Cochrane tool. Results 30 RCTs with 2283 participants were included. Very low quality of evidence was found for positive effects of yoga on systolic blood pressure (SBP, 26 RCTs, n = 2007; MD = -7.95 mmHg, 95% CI = -10.24 to -5.66, p < 0.01), diastolic blood pressure (DBP, 23 RCTs, n = 1836; MD = -4.93 mmHg, 95% CI = -6.25 to -3.60, p < 0.01) and heart rate (HR, 14 RCTs, n = 1118; MD = -4.43 mmHg, 95% CI = -7.36 to -1.50, p < 0.01) compared to waitlist control. Compared to active control, very low quality of evidence was found for positive effects yoga on SBP (5 RCTs, n = 306; MD = -4.16 mmHg, 95%CI = -10.76 to 2.44, p = 0.22), DBP (5 RCTs, n = 306; MD = -1.88 mmHg, 95%CI = -3.41 to -0.36, p = 0.02) and HR (2 RCT, n = 128; MD = -5.16 mmHg, 95% CI = -8.39 to -1.92, p < 0.01). Overall, the studies showed a high degree of heterogeneity. The effects found were robust against selection, detection and attrition bias. Conclusion Yoga may be an option for lowering blood pressure in people with prehypertension to hypertension. More and larger high-quality studies are needed to substantiate our findings.